The Development of Social Inclusion-Based Library in Pesing Village, Purwoasri District, Kediri, East Java - Ragil Tri Atmi; Tri Soesantari; Endang Gunarti; Imam Yuadi; Fitri Mutia; Yunus Abdul Halim (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The development of a social inclusion-based library located in Pesing Village, Purwoasri District, Kediri, can raise the welfare of the local community through the use of the collections provided. In this community service, socialization is given to participants who come from the local community, represented by village officials, teachers, youth organizations, while the material presented is the concept and implementation of Social Inclusion-Based Libraries and how to collection management like make collection subjects, classify collections to choose the right collection. for the community according to their livelihood. The Department of Information and Library of Airlangga University as the organizer of the activity also donated various collections, covering themes of agriculture, plantations, fishery sector development, and many other general themes that can be utilized to develop the economic activities of the local community. Social inclusion through village library services deserves to be counted as the main driving force for all community activities. Through the collections provided by the village library, it is hoped that the community can develop their skills and knowledge to produce a variety of new livelihoods, and have a real impact on improving the welfare of their families. Through the training for village library managers, it was found that their understanding of libraries became wider, including they began to understand how to manage collections in accordance with library management rules